The use of personal pronoun in Donald Trump’s speech - Nafilatun Nasuha; Rosyida Ekawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
This study concerns with the use of personal pronouns in political speech. The aims of this study are to find out personal pronouns used in Donald Trump’s speech and their functions. The source of data of this research is the speech by Donald trump at 74th session of the united nation general assembly. This study used descriptive qualitative method. The result shows that Donald Trump used personal pronoun I to emphasize his authority and his good qualities such as confident, share experience, and opinion. Personal pronoun you is used to refer to a specific group when he wants to separate one group from other groups. He also used you to refer to general to avoid conflict. He used personal pronoun inclusive we to involve himself with the united nation member. He used exclusive we to show his good relation with other groups in sharing responsibility. He used personal pronouns they to make him and the united nation members less responsible for other groups activities.